Analysis of Marketing Strategy and Break-Even Points of Cassava Leaf Chips for MSMEs in Alaspandan - Aliph Erwansyah; Mochammad Ilyas Junjunan (Institut Agama Islam Al-Fatimah Bojonegoro, 2024)
Micro and medium-sized enterprises are important in driving the local economy, especially in rural areas such as Alaspandan Village, which has natural potential in cassava leaves. Processing cassava leaves into chips produces added value and opens up employment opportunities for the local community. This study analyzes the marketing strategy and calculation of the Break-Even Point (BEP) in the